A Newmark space‐time approach in structural mechanics. Issue 1 (25th January 2021) - Bamer, Franz; Shirafkan, Nima; Cao, Xiaodan; Oueslati, Abdelbacet; Stoffel, Marcus; De Saxcé, Géry; Markert, Bernd
Abstract: In this contribution, we present a non‐incremental time integration scheme using the implicit Newmark approximations. The result is one space‐time equation that can be solved using the proper general decomposition ansatz.